Post-globalization and prospects of social development - Ivanov, Dmitry V. (Journal of the Belarusian State University. Sociology, 2020)
The article presents a new approach to measure level of social development for societies facing the post-globalization as globalizing networks and flows paradoxically are localized in super-urban areas where people experience borderless, multicultural, and mobile social life in the regime of augmented modernity. In the post-globalization age, the ‘core’ of socioeconomic order is dispersed into networks of enclaves of augmented modernity contrasting with exhausted modernity outside them. The nations’ prospects of social development depend on number, size, and influence of cosmopolitan superurban areas attracting and generating transnational material, human, and symbolic flows.